Continent‐wide patterns of song variation predicted by classical rules of biogeography. (20th September 2022) - Sebastianelli, Matteo; Lukhele, Sifiso M.; Nwankwo, Emmanuel C.; Hadjioannou, Louis; Kirschel, Alexander N. G.
Abstract: Physiological constraints related to atmospheric temperature pose a limit to body and appendage size in endothermic animals. This relationship has been summarised by two classical principles of biogeography: Bergmann's and Allen's rules. Body size may also constrain other phenotypic traits important in ecology, evolution and behaviour, and such effects have seldom been investigated at a continental scale. Through a multilevel‐modelling approach, we demonstrate that continent‐wide morphology of related African barbets follows predictions of Bergmann's rule, and that body size mirrors variation in song pitch, an acoustic trait important in species recognition and sexual selection. Specifically, effects on song frequency in accordance with Bergmann's rule dwarf those of acoustic adaptation at a continental scale. Our findings suggest that macroecological patterns of body size can influence phenotypic traits important in ecology and evolution, and provide a baseline for further studies on the effects of environmental change on bird song. Abstract : Temperature‐related physiological constraints shape functional traits in animals at a global scale, yet the implications of continent‐wide morphological variation on acoustic communication signals is little understood. This is despite a well‐established relationship between body size and acoustic signal frequencies across the animal kingdom. In a continent‐wide study on birds, we show that song frequency mirrors predictable patterns of body size variation along a latitudinal and elevational gradient, suggesting climate change may drive predictable shifts in the frequency of acoustic signals that play a critical role in animal ecology and evolution.